Aboriginal Youth Talk about Structural Determinants as the Causes of their Homelessness - Baskin, Cyndy (First Peoples Child & Family Review)

(untitled) (First Nations Child and Family Caring Society of Canada, 2007)
This article explores structural determinants as possible causes of the homelessness of Aboriginal youth in Toronto, Ontario, Canada. It includes a brief literature review and provides some of the ﬁndings of a recent research project, which implemented an Aboriginal research methodology with homeless youth in Toronto. These ﬁndings point to a strong link between Aboriginal children growing up in poverty and involvement in child welfare and becoming homeless as youth. Suggestions for positive change at the policy level are offered in order to prevent the next generation of Aboriginal children growing up to become homeless youth.